Mechanisms That Modulate and Diversify BDNF Functions: Implications for Hippocampal Synaptic Plasticity - De Vincenti, Ana Paula; Ríos, Antonella S.; Paratcha, Gustavo; Ledda, Fernanda (Frontiers in Cellular Neuroscience, 2019)
Brain-Derived Neurotrophic Factor (BDNF) is a neurotrophin that has pleiotropic effects on neuronal morphology and synaptic plasticity that underlie hippocampal circuit development and cognition. Recent advances established that BDNF function is controlled and diversified by molecular and cellular mechanisms including trafficking and subcellular compartmentalization of different Bdnf mRNA species, pre- vs. postsynaptic release of BDNF, control of BDNF signaling by TrkB receptor interactors and conversion of pro-BDNF to mature BDNF and BDNF-propeptide. Defects in these regulatory mechanisms affect dendritic spine formation and morphology of pyramidal neurons as well as synaptic integration of newborn granule cells (GCs) into preexisting circuits of mature hippocampus, compromising the cognitive function. Here, we review recent findings describing novel dynamic mechanisms that diversify and locally control the function of BDNF in hippocampal neurons.